2022
DOI: 10.1021/acschembio.2c00657
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking a Linaridin Biosynthetic Intermediate for Lanthipeptide Production

Abstract: Linaridins and lanthipeptides are two classes of natural products belonging to the ribosomally synthesized and posttranslationally modified peptide (RiPP) superfamily. Although these two RiPP classes share similar structural motifs such as dehydroamino acids and thioether-based cross-links, the biosynthesis of linaridins and lanthipeptides involved distinct sets of enzymes. Here, we report the identification of a novel lanthipeptide cypepeptin from a recombinant strain of Streptomyces lividans, which harbors m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In this study, we demonstrated that cypemycin is a previously uncharacterized, d -amino acid-rich linaridin. A similar conclusion was reported by Zhang et al during the manuscript review process . In particular, we provide access to the family-determining activity of CypH and CypL, which are two membrane-associated proteins unique to linaridin formation, based on heterologous reconstitution of the cypemycin pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated that cypemycin is a previously uncharacterized, d -amino acid-rich linaridin. A similar conclusion was reported by Zhang et al during the manuscript review process . In particular, we provide access to the family-determining activity of CypH and CypL, which are two membrane-associated proteins unique to linaridin formation, based on heterologous reconstitution of the cypemycin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was reported by Zhang et al during the manuscript review process. 20 In particular, we provide access to the familydetermining activity of CypH and CypL, which are two membrane-associated proteins unique to linaridin formation, based on heterologous reconstitution of the cypemycin pathway. As in S. coelicolor, the cooccurrence of CypH and CypL is necessary and sufficient for the formation of a highly modified linaridin RiPP, by transforming the CypA precursor peptide through three types, 16 PTMs in total in its CP sequence, that is, 11 epimerization reactions, 4 Thr dehydrations, and 1 Cys dethiolation, followed by hydrolysis by removal of the LP sequence to achieve linaridin 5.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…S5 and S6, ESI†) and linaridins. 32,33 Although we cannot rule out that during purification minor products may have been removed that could contain ( Z )-Dhb, these results clearly demonstrate that the predominant product of mSptA (1–37)trypsin contains an ( E )-Dhb and not a ( Z )-Dhb residue. To our knowledge, this represents the first example of detection of a peptide containing an ( E )-Dhb residue with ribosomal origin.…”
mentioning
confidence: 76%
“…Cypemycin had been proposed to contain an ( E )-Dhb, but that proposal was recently shown to be incorrect. 32 Therefore, the GL SptB b in SapT biosynthesis catalyzes net syn -elimination of glutamylated Thr residues to form ( E )-Dhb residues. Subsequent anti -addition of l -Cys across the Si face of the ( E )-Dhb residue by SptC then forms d - allo - l -MeLan macrocycles found in SapT.…”
mentioning
confidence: 99%
“…OH-4156 in 1993 and is structurally characterized by the presence of four Dhb residues, a 2-aminovinyl-cysteine (AviCys) moiety, and an N , N -dimethylalanine. Recently, the structure of cypemycin was reinvestigated by two independent studies through heterologous expression of the cyp BGC in S . lividans 66 and S. coelicolor , respectively, and was found to contain 12 epimerized amino acid residues (Figure A, bottom structure).…”
mentioning
confidence: 99%